Autophagy protects pancreatic beta cell mass and function in the setting of a high-fat and high-glucose diet. Issue 1 (December 2017) - Sheng, Qingfeng; Xiao, Xiangwei; Prasadan, Krishna; Chen, Congde; Ming, Yungching; Fusco, Joseph; Gangopadhyay, Nupur; Ricks, David; Gittes, George
Abstract Autophagy is a major regulator of pancreatic beta cell homeostasis. Altered autophagic activity has been implicated in the beta cells of patients with type 2 diabetes, and in the beta cells of obese diabetic rodents. Here, we show that autophagy was induced in beta cells by either a high-fat diet or a combined high-fat and high-glucose diet, but not by high-glucose alone. However, a high-glucose intake alone did increase beta cell mass and insulin secretion moderately. Depletion of Atg7, a necessary component of the autophagy pathway, in beta cells by pancreatic intra-ductal AAV8-shAtg7 infusion in C57BL/6 mice, resulted in decreased beta cell mass, impaired glucose tolerance, defective insulin secretion, and increased apoptosis when a combined high-fat and high-glucose diet was given, seemingly due to suppression of autophagy. Taken together, our findings suggest that the autophagy pathway may act as a protective mechanism in pancreatic beta cells during a high-calorie diet.